Squamous cell carcinoma arising from chronic osteomyelitis massively expanding into the medullary cavity: A case report - Taisei Kurihara; Yoshiyuki Suehara; Keisuke Akaike; Takuo Hayashi; Taketo Okubo; Youngji Kim; Tatsuya Takagi; Kazuo Kaneko; Takashi Yao; Tsuyoshi Saito (Elsevier, 2019)
An 80-year-old man was diagnosed with squamous cell carcinoma (SCC) arising from chronic osteomyelitis in his right femur. The pathological findings of the amputated leg showed ulcerated tumor extending from the skin to the medullary cavity of the right femur in a continuous fashion. Metastasis in the left clavicle was also noticed 6 months after surgery, and the patient ultimately died 8 months after the operation. A review of the previous literature showed that SCCs arising from chronic osteomyelitis which widely extended to the bone marrow are quite rare. A careful pathological evaluation, such as cytological examination from bone marrow washing, might be necessary and useful for early detection of malignant neoplasms arising from osteomyelitis, although not performed in this case. Keywords: Osteomyelitis, Squamous cell carcinoma, Malignant transformation